Rain as Emotion and Renewal: Exploring Symbolism in Ten Modern Poems - Mariwan Hasan (Universitas Tidar, 2025)
This paper explores the multifaceted symbolism of rain in ten modern poems, examining its role as a vehicle for emotional comfort amid the struggles of human existence. Drawing on works by poets such as Mary Oliver, Langston Hughes, Pablo Neruda, and Edgar Allan Poe, the analysis reveals how rain operates as both a metaphor for melancholy and a catalyst for renewal. Using a comparative thematic approach grounded in close textual analysis, the study investigates how rain imagery reflects intersections between emotion, culture, and environment in modern poetic expression. The discussion highlights how rain imagery serves personal introspection, cultural identity, and collective healing, especially in contexts marked by historical hardship or environmental scarcity. The paper’s novel contribution lies in its synthesis of emotional and ecological readings of rain symbolism, demonstrating how this natural motif bridges inner psychological states and broader cultural narratives. By tracing the dual nature of rain—as a source of sadness and as a rejuvenating force—the paper underscores its enduring thematic relevance in modern poetry.